Analisis Etika Bisnis Islam terhadap Promosi Online dan Ulasan Pengguna terkait Keputusan Pembelian Alas Kaki Bermerek Palsu di Kalangan Konsumen Shopee di Cirebon dalam Rangka Mendorong Praktik E-Commerce Halal - Muhammad Azmi; May Dedu (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2026)
This study aims to analyze the influence of online promotion and user reviews on consumers' purchasing decisions in Cirebon City regarding counterfeit branded footwear on the Shopee marketplace. Employing a quantitative approach with a survey design, data were collected from 120 respondents via purposive sampling and analyzed using multiple linear regression. The results indicate that both online promotion and user reviews, whether considered individually or simultaneously, have a positive and significant impact on the decision to purchase counterfeit products. However, the coefficient of determination (R²) of only 9.4% suggests that factors outside the research model influence 90.6% of the variation in purchasing decisions. The novelty of this study lies in its integration of Islamic business ethics as an analytical framework for understanding digital consumer behavior. These findings offer strategic implications: curbing the consumption of counterfeit goods through the application of Islamic business ethics is not only vital for promoting halal e-commerce practices but is also crucial for socio-economic strengthening. By shifting consumer purchasing power from counterfeit goods to authentic local products, the digital market ecosystem can become more equitable, respectful of intellectual property rights, and supportive of inclusive and sustainable real economic growth.